2022
DOI: 10.18421/sar51-04
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Integrated Marketing Communications on Customer Purchasing Decision in Yemen's Telecommunications Industry

Abstract: Nowadays, in the world of competition, customers seem to be fortunate. Since they have various alternative services and products, companies look for satisfying customers by providing good quality, price and promotion. So, entrepreneurs have to employ various means to stay competitive on the markets. This study aimed to investigate if the integrated marketing communications (IMC) of GSM companies have an impact on customers purchasing decision. The target population of this study were the customers of the GSM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This advancement has reduced the rate at which customers changes their service providers from one telecommunication product to another. However, customer's buying decisions solely depends on the best service and benefit provider amongst the telecommunication products (Abimbola et al, 2020;Qasem et al, 2022). It has been revealed that the market share of the telecommunication companies has been affected due to the fierce competition amongst the companies in Yemen.…”
Section: Problem Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…This advancement has reduced the rate at which customers changes their service providers from one telecommunication product to another. However, customer's buying decisions solely depends on the best service and benefit provider amongst the telecommunication products (Abimbola et al, 2020;Qasem et al, 2022). It has been revealed that the market share of the telecommunication companies has been affected due to the fierce competition amongst the companies in Yemen.…”
Section: Problem Statementmentioning
confidence: 99%
“…This have reflected in customers' decisions to use cellular services provided by the four companies operating in Yemen. Studies have indicated that for a company to gain relevance and most preferred by the consumers as well as compete in a larger market share, it has focus much on promotional activities geared towards ensuring a greater competitive advantage (Abimbola et al, 2020;Al-sharafi et al, 2018;Qasem et al, 2022). Hence, promotional activities such as; sales promotion, advertising, personal selling, public relations and publicity are all considered as marketing efforts used in presenting company's products, its features, as well as what distinguish it from other products (Alananzeh et al, 2018;Clow & Donald, 2017).…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations